Mapping Retail Service Quality and Customer Satisfaction in Emerging Markets (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study focuses on examining the impact  of quality of services on the satisfaction of  customers with samples drawn from NCR.  Data related to service quality parameters were  collected from 325 respondents using Retail  Service Quality Scale (RSQS). Customer  satisfaction was measured using four items  taken from the scale developed by Bitner and  Hubbert (1994). Exploratory factor analysis  (EFA) was used to achieve the first objective  and Stepwise regression was applied for second  objective. During rotation method, 26 items  were reduced to five factors and were named after  original factors given in the RSQS. EFA revealed  that RSQS is partially applicable in Indian  retail context and regression results shown that  three factors of service quality; PA (Physical  Appearance), PI (Personal Interaction) and PS  (Problem Solving) have significant contribution  to service quality while assessing the customer  satisfaction.
Keywords: Customer Satisfaction; Retail Store; Service Quality; Emerging Market; RSQS